Person Centered Psychiatry - Mezzich, Juan E.; Botbol, Michel; Christodoulou, George N.; Cloninger, C. Robert; Salloum, Ihsan M. (Springer International Publishing : Imprint: Springer, 2016)
This book presents an authoritative overview of individualized psychiatry. The text shifts the focus of psychiatry from organ and disease to the whole person as a part of a broader person-centered perspective in medicine. Written by experts in the field, the text covers the conceptual keystones of that include ethical commitment, a holistic approach, a relationship focus, cultural sensitivity, individualized care, establishment of common ground among clinicians, patients, and families for joint diagnostic understanding and shared clinical decision-making, people-centered organization of services, and person-centered health education and research. Person-Centered Psychiatry is an excellent resource for psychiatrists, psychologists, primary care physicians, social workers, and all medical professionals working in mental health.